Digital Transformation of Police Supervision and Its Implications for the Principle of Checks and Balances in the Indonesian Constitutional System - Paulus Wisnu Yudoprakoso (Jurnal Daulat Hukum, 2026)
Within Indonesia’s post-reform constitutional order, the Indonesian National Police (Polri) functions as a civilian institution within the executive branch while exercising broad powers that have a direct impact on the protection of citizens’ rights and fundamental freedoms. In practice, conventional oversight mechanisms over Polri often face structural and institutional constraints, particularly in ensuring transparency and accountability. The development of digital technology has introduced new forms of public-based oversight, enabling broader civic participation through digital reporting platforms and online monitoring. This study examines the digital transformation of Polri oversight as a constitutional phenomenon and analyzes its implications for the checks and balances principle. Using a normative juridical method with statutory and conceptual approaches, this research finds that digital oversight may strengthen constitutional accountability by expanding public scrutiny and access to information. Nevertheless, without a clear normative and institutional framework, digital oversight risks producing fragmented control mechanisms that operate outside formal accountability structures and potentially undermine due process of law. Therefore, the integration of digital oversight must be constitutionally designed to reinforce, rather than replace, established mechanisms of power limitation in a democratic constitutional state.